Online identification of drowsy driver using expert system / Ruzelita Ngadiran ... [et al.] - Ngadiran, Ruzelita; Mohd Nor, Mohd Jailani; Md Saad, Mohd Hanif; Koh, Wei Kiat (2004)
This paper discusses the use of Expert System for identification of drowsy driver. To investigate the effectiveness of the usage of Expert System in identifying drowsy driver, a system consisting of data acquisition system and a Forward Chaining reasoning engine was developed in this study. The Knowledge Base (KE) for this system was developed based on previous study of drowsy driver. A K.B development tool, the Simple Expert System Development Tool (SESDT) , was used to generate the rules. Altogether, the system that was developed in this study consists of 98 rules. The rules combines' effects from five parameters to identify drowsiness (time of driving, period of driving, head movement along Y-axis, steering wheel reversal rate and Percentage of Eye Closure (PERCLOS). Preliminary results were promising and it was observed that The Expert System was able to sufficiently identify drowsy driver using the above reasoning engine and KB.